2000
DOI: 10.1017/s0305000900004232
|View full text |Cite
|
Sign up to set email alerts
|

Late-talking toddlers: MLU and IPSyn outcomes at 3;0 and 4;0

Abstract: Expressive language outcomes measured by MLU and the Index of Productive Syntax (IPSyn) at ages 3;0 and 4;0 were investigated in 34 late talkers with normal receptive language identified between 2;0 to 2;7 and 16 typically developing comparison children matched on age, SES, and nonverbal ability. Late talkers made greater gains than comparison children between 3;0 and 4;0 in both MLU and IPSyn raw score. However, when age-standardized z-scores were analysed, the late talkers were about 2·5 standard devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
1
13

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 36 publications
3
78
1
13
Order By: Relevance
“…Although here we will not examine literacy, and will only review a small proportion of the literature on spoken language in school-age children where it elucidates other points, early spoken language abilities are highly predictive of preschool and school performance in typically developing children, including those at risk and those in poverty (Hoff, 2003;Locke, Ginsborg, & Peers, 2002;Molfese, Molfese, & Modgline, 2001;Noble, Norman, & Farah, 2005;Pan, Rowe, Spier, & Tamis-Lemonda, 2004;Rescorla, Dahlsgaard, & Roberts, 2000), and in a setting where children have limited opportunities for education, it is important to maximise school readiness.…”
Section: Introductionmentioning
confidence: 99%
“…Although here we will not examine literacy, and will only review a small proportion of the literature on spoken language in school-age children where it elucidates other points, early spoken language abilities are highly predictive of preschool and school performance in typically developing children, including those at risk and those in poverty (Hoff, 2003;Locke, Ginsborg, & Peers, 2002;Molfese, Molfese, & Modgline, 2001;Noble, Norman, & Farah, 2005;Pan, Rowe, Spier, & Tamis-Lemonda, 2004;Rescorla, Dahlsgaard, & Roberts, 2000), and in a setting where children have limited opportunities for education, it is important to maximise school readiness.…”
Section: Introductionmentioning
confidence: 99%
“…It has often been hypothesized that the first speech-like articulation and the babbling phase, which occur at approximately 10 months of age, allow infants to develop a link between articulatory settings and the resulting auditory consequences, thus laying down the basis for the development of the phonetic inventory and adaptation to the ambient language (Westermann and Miranda, 2004). Several longitudinal studies, conducted on different populations and using different modes of analysis, indicated a continuity between prelinguistic production (babbling) and first words both in typically developing children (Bates, Benigni, Bretherton, Camaioni and Volterra, 1979;Leonard and Bortolini, 1998;Locke, 1989;Oller, Eilers, Neal and Schwartz, 1999;Vihman and McCune, 1994) and in children with language delay (D'Odorico, Bortolini, De Gasperi and Assanelli, 1999;Oller, Eilers, Neal and Cobo-Lewis, 1998;Rescorla, Dahlsgaard and Roberts, 2000;Stoel-Gammon, 1989).…”
mentioning
confidence: 99%
“…Kõne hindamiseks on vaja teada tunnuseid, mis eristavad kõnehilistusega lapsi eakohase aren guga lastest. Eelkõige inglise keele baasil tehtud uuringutest (Rescorla, 2011;Rescorla, Dahlsgaard, & Roberts, 2000;Rescorla & Roberts, 2002;Rescorla & Turner, 2015;Rice, Taylor, & Zubrick, 2008) ilmneb, et hilis kõnelejatele on iseloomulik grammatiliste oskuste, eriti verbimorfoloogia hilisem kujune mine. Just 3-4aastastel kõne arengu hilistusega lastel on grammatiliste oskuste tase eakohase arenguga laste omast madalam, samas 5-6aastastel hakkab see jõudma eakaaslastele järele.…”
Section: Sissejuhatusunclassified
“…Seega on tegemist vaid ühe arenguvaldkonna -kõne -ebatüüpi lise arenguga, mille aluseks peetakse keele omandamise võime nõrkust (Rescorla et al, 2000;Rescorla & Turner, 2015). Kõne arengu hiline algus on seotud neurobioloogilise ja geneetilise mehhanismiga: üheks pea miseks riski faktoriks kõnehilistumise tekkel on peres esinevad keelepuuded ja lugemiskirjutamisraskused (Desmarais et al, 2008;Everitt et al, 2013;Hawa & Spanoudis, 2014).…”
Section: Kõne Arengu Hilistuse Ehk Peetusega Lapsedunclassified
See 1 more Smart Citation